2002
DOI: 10.1100/tsw.2002.157
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Selection of Hypoallergenic Buckwheat Species

Abstract: Both common buckwheat (Fagopyrum esculentum) flour and meal cause an allergy in sensitive patients, and if unnoticed, it can be fatal. It has become a potential occupational hazard for some mill workers. The development of hypoallergenic buckwheat would be more efficient if natural mutants for allergenic protein are detected. A screening and selection method was developed using SDS-PAGE coupled with PCR techniques. SDS-PAGE analysis of 14 different species of buckwheat revealed that F. lineare and F. urophyllu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Recently, several genomic clones corresponding to 13S buckwheat globulin have been characterized. The acidic and basic polypeptides were found to contain 293 and 191 amino acids, respectively, and the calculated M w of 13S buckwheat globulin was 342,258 Da (Fujino, Funatsuki, Inada, Shimono, & Kikuta, 2001;Nair & Adachi, 2002;Nair, Ohmoto, Woo, & Adachi, 1999;Samardzic, Milisavljevic, & Brkljacic, 2004).…”
Section: Sodium Dodecyl Sulfate Polyacrylamide Gel Electrophoresismentioning
confidence: 99%
“…Recently, several genomic clones corresponding to 13S buckwheat globulin have been characterized. The acidic and basic polypeptides were found to contain 293 and 191 amino acids, respectively, and the calculated M w of 13S buckwheat globulin was 342,258 Da (Fujino, Funatsuki, Inada, Shimono, & Kikuta, 2001;Nair & Adachi, 2002;Nair, Ohmoto, Woo, & Adachi, 1999;Samardzic, Milisavljevic, & Brkljacic, 2004).…”
Section: Sodium Dodecyl Sulfate Polyacrylamide Gel Electrophoresismentioning
confidence: 99%
“…11,12) Besides, it has been reported that some allergenic proteins of cultivated buckwheat might be distributed among the Fagopyrum spp. 13,14) Thus, the risk of raising the buckwheat allergy due to allergens derived from wild buckwheat may be relatively high. A method to detect the presence of all the Fagopyrum spp.…”
mentioning
confidence: 99%
“…Although most of them are quantitative methods which are laborious and time consuming, protein-based methods and PCR-based detection methods are also available (Hirao et al 2005;Jeon et al 2007;Yamakawa et al 2008;Yoon et al 2010). However, it is hard to evaluate whether these methods can detect the variation among the two buckwheat species as most of the proteins found in common and Tartary buckwheat are similar (Nair & Adachi 2002). Hence, a method to detect two cultivated buckwheat species is required for the authentication of buckwheat products.…”
Section: Discussionmentioning
confidence: 99%